Cyclic Voltammetry, Impedance and Thermal Properties of CoFe2O4 Obtained from Waste Li-Ion Batteries. (2018) - Mylarappa, M.; Venkata Lakshmi, V.; Vishnu Mahesh, K.R.; Raghavendra, N.; Nagaswarupa, H.P.
Abstract: In the present study, CoFe2 O4 nanocrystals were synthesized from waste lithium ion battery powder using citric acid as eco- friendly material by hydrothermal method. The prepared materials were characterized by X-ray powder diffraction (XRD) to study particle size and crystallinity, the morphology of the nano composite are analysed by using Scanning Electron Microscopy (SEM), functional group were observed using Fourier Transform Infrared Spectrometer (FTIR). The thermal properties of CoFe2 O4 nanocrystals were analysed using Thermo Gravimetric Analysis (TGA), Differential Scanning Calometry (DSC) and Differential Thermal Analysis. The synthesized nano particle was studied for the electrochemical studies such as Cyclic Voltammetry (CV), electrochemical impedance spectra, capacitance and electron transfer resistance